(untitled) (Academicia Globe: Inderscience Research, 2024)
This paper gives information about what does actual commodity market stand for and shows how this market has been developing and contributing to the economy of Uzbekistan. The foreign trade data is taken from the OEC website where the share of the commodity market’s elements in export and import until 2023 is illustrated in percentages. Also, several challenges and opportunities for economic diversification will be outlined in terms of commodity markets.